Emigration and Wages: The EU Enlargement Experiment - Benjamin Elsner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The enlargement of the European Union in 2004 caused a large migration wave from Central Europe to Ireland and the UK. This paper addresses the question whether such an emigration wave changes the wage distribution in the source country. In a theoretical model of a labor market I show that some groups of stayers gain, while others lose from emigration. This outcome depends on the degree of subsitutability between different groups of workers, as well as on skill distribution of emigrants. Using microdata from Lithuania, I simulate the post-2004 emigration wave based on the theoretical model and calculate the resulting changes in wages for different groups of workers. I nd that the wages of young workers increased by around 6% while the wages of older workers decrease by around 2%. The wage increase for young workers is the result of the supply shift: most of the emigrants were young, so that young workers who stay behind become a more scarce resource in the labor market. At the same time, the emigration of young workers decreases the labor demand for older workers, which results in a decrease of their wages.
Keywords: F22; J31; O15; 330; Emigration; EU Enlargement; European Integration; Wage Distribution